2007
DOI: 10.1289/ehp.10506
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated Chemicals and Fetal Growth: A Study within the Danish National Birth Cohort

Abstract: BackgroundPerfluorooctanesulfonate (PFOS) and perfluorooctanoate (PFOA) are man-made, persistent organic pollutants widely spread throughout the environment and human populations. They have been found to interfere with fetal growth in some animal models, but whether a similar effect is seen in humans is uncertain.ObjectivesWe investigated the association between plasma levels of PFOS and PFOA in pregnant women and their infants’ birth weight and length of gestation.MethodsWe randomly selected 1,400 women and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

53
516
19
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 565 publications
(602 citation statements)
references
References 40 publications
53
516
19
14
Order By: Relevance
“…PFCs have been shown to cross the placenta (Inoue et al 2004;Liu et al 2011;Gützkow et al 2012) and thus have a potential to exert a direct influence on the developing fetus (Apelberg et al 2007a;Fei et al 2007). According to previous studies, the median PFC concentrations in cord blood ranged from 30 to 130% of the maternal concentrations (Liu et al, 2011, Kim et al 2011a, Gützkow et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PFCs have been shown to cross the placenta (Inoue et al 2004;Liu et al 2011;Gützkow et al 2012) and thus have a potential to exert a direct influence on the developing fetus (Apelberg et al 2007a;Fei et al 2007). According to previous studies, the median PFC concentrations in cord blood ranged from 30 to 130% of the maternal concentrations (Liu et al, 2011, Kim et al 2011a, Gützkow et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The potential determinants of maternal and fetal exposure to PFCs are poorly investigated and their potential to affect the concentrations of PFCs in pregnant women and fetuses is still unclear. Some studies have shown that PFOS levels are higher in black women than in white and Asian women (Apelberg et al 2007b) and are also higher in nonsmokers than smokers (Fei et al 2007;Washino et al 2009). The PFOA levels decrease with increasing maternal age (Washino et al 2009), BMI (Fei et al 2007), and parity (Fei et 4 al.…”
Section: Introductionmentioning
confidence: 99%
“…PFOS and perfluorooctanoic acid (PFOA) are typical representative chemicals for PFSAs and PFCAs. Because of the high energy carbon-fluorine covalent bond, PFCAs and PFSAs are persistent against the typical environmental degradation processes, and longer chain PFCAs and PFSAs are bio-accumulative (Martin et al, 2003) and have potential adverse effects on humans and animals (Kudo and Kawashima, 2003;Fei et al, 2007). As a result, PFOS and its salts together with its precursor, perfluorooctane sulfonyl fluoride (POSF), were listed to Annex B of the Stockholm Convention in 2009, calling for restricted production and use worldwide (UNEP, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[53] Maternal blood concentrations of PFOA, but not PFOS, were negatively associated with birthweight in newborns from Denmark. [54] A further study reported a statistically significant negative correlation between abdominal circumference and maternal PFOA, a statistically significant positive association between ponderal index to maternal PFOA of women who were obese before pregnancy, and a statistically non-significant negative correlation between head circumference and maternal PFOA. [54] These findings suggested that PFOS and PFOA may affect the growth of organs and skeleton in infants and can have adverse effects on overall fetal growth and neonatal development.…”
Section: Human Exposure Pathways and Need For Epidemiologic Studiesmentioning
confidence: 91%
“…[54] A further study reported a statistically significant negative correlation between abdominal circumference and maternal PFOA, a statistically significant positive association between ponderal index to maternal PFOA of women who were obese before pregnancy, and a statistically non-significant negative correlation between head circumference and maternal PFOA. [54] These findings suggested that PFOS and PFOA may affect the growth of organs and skeleton in infants and can have adverse effects on overall fetal growth and neonatal development. However, the literature results are inconsistent, suggesting the influence of several confounding factors, which need to be carefully controlled for, in epidemiological data analysis and interpretation.…”
Section: Human Exposure Pathways and Need For Epidemiologic Studiesmentioning
confidence: 91%